Предмет: Алгебра,
автор: victoryaignatova2805
Докажите тождество:
(х-4)(х+1)=х(х-3)+4
Ответы
Автор ответа:
4
(х-4)(х+1)=х(х-3)+4
Откроем скобки:
Приведем подобные:
-3х-4=-3х+4
Закончим приведения подобных:
-4=4
Равенство неверно. Тождество не доказано. т.е утверждение неверно
Откроем скобки:
Приведем подобные:
-3х-4=-3х+4
Закончим приведения подобных:
-4=4
Равенство неверно. Тождество не доказано. т.е утверждение неверно
Похожие вопросы
Предмет: Математика,
автор: Andreeey20
Предмет: Қазақ тiлi,
автор: bspenny417
Предмет: Алгебра,
автор: nassvis
Предмет: Литература,
автор: Вероника2803
Предмет: Математика,
автор: Ламповая2005